Algorithmic Approaches for Storage Networks - Salzwedel, Kay A. (Algorithms for Memory Hierarchies)

Storage Management as Means to cope with Exponential Information Growth - Scheideler, Christian; Salzwedel, Kay; Meyer auf der Heide, Friedhelm; Brinkmann, André; Vodisek, Mario; Rückert, Ulrich (Proceedings of SSGRR 2003)
The advances in Internet technology have led to tremendous improvements in business, education, and science and have changed the way we think, live, and communicate. Information exchange has become ubiquitous by the possibilities offered through modern technologies. We are able to offer information 24 hours a day through our web sites and can leave messages every time and from anywhere in the world. This change in communication has led to new challenges. Enterprises have to deal with an information amount that doubles every year. The technological foundation to cope with this information explosion is given by Storage Area Networks (SANs), which are able to connect a great number of storage systems over a fast interconnection network. However, to be able to use the benefits of a SAN, an easy-to-use and efficient management support has to be given to the storage administrator. In this paper, we will suggest new storage management concepts and we will introduce a new management environment that is able to significantly reduce management costs and increases the performance and resource utilization of the given SAN infrastructure.

Performance of distributed algorithms for topology control in wireless networks - Rührup, Stefan; Schindelhauer, Christian; Volbert, Klaus; Grünewald, M. (Proceedings of the International Parallel and Distributed Processing Symposium (IPDPS))
We try to close the gap between theoretical investigations of wireless network topologies and realistic wireless environments. For point-to-point communication, we examine theoretically well-analyzed sparse graphs, i.e. the Yao-graph, the SparsY-graph, and the SymmY-graph. We present distributed algorithms that can be used to build up these graphs in time $O(log n)$ per node without the use of any geo-graphical positioning system. Our algorithms are based only on local knowledge and local decisions and make use of power control to establish communication links with low energy-cost. We compare these algorithms with respect to congestion, dilation, and energy. For congestion we introduce different measures that allow us to investigate the difference between real-world wireless networks and models for wireless communication at a high level of abstraction. For more realistic simulations we extend our simulation environment SAHNE. We use a realistic transmission model for directed communication that uses sector subdivision. Finally, our experimental results show that our topologies and algorithms work well in a distributed environment and we give some recommendations for the topology control based on our simulations.

Implementierung und Vergleich von Verfahren zum Information Retrieval im World Wide Web - Mahlmann, Peter

Directed power-variable infrared communication for the mini robot Khepera - Volbert, Klaus; Grünewald, Matthias; Schindelhauer, Christian; Rückert, Ulrich (Proceedings of the 2nd International Conference on Autonomous Minirobots for Research and Edutainment)
Communication facilities are important in Robotics if several robots have to work together. In this paper, we describe problems and solutions encountered while designing an infrared-based communication device for the mini robot Khepera. In contrast to traditional omnidirectional systems, it features directed, power-variable transmission in eight directions at unit[23.4]kbps up to a range of unit[1m]. It can differentiate incoming data signals from interference from adjacent sectors and can estimate their direction-of-arrival. We model the transmission over the infrared channel and show how interference influences the reception of the data signals. We also describe methods how to reduce these effects. We have tested the performance of the resulted signal processing in a worst case scenario by simulations and in experiments with a prototype implementation. The resulted module is especially suited for experimental evaluation of ad hoc network protocols and for position estimation.

ADB-Trees: Controlling the Error of Time-Critical Collision Detection - Klein, Jan; Zachmann, Gabriel (Proc. 8th International Fall Workshop Vision, Modeling, and Visualization (VMV 2003))
We present a novel framework for hierarchical collision detection that can be applied to virtually all bounding volume (BV) hierarchies. It allows an application to trade quality for speed. Our algorithm yields an estimation of the quality, so that applications can specify the desired quality. In a timecritical system, applications can specify the maximum time budget instead, and quantitatively assess the quality of the results returned by the collision detection afterwards.

Time-Critical Collision Detection Using an Average-Case Approach - Klein, Jan; Zachmann, Gabriel (Proc. ACM Symposium on Virtual Reality Software and Technology (VRST 2003))

"Irgendwie anders?!" Ein Kinderbuchprojekt zur Förderung der Selbst- und Fremdwahrnehmung. Arbeitsgruppe im Rahmen des 3. Paderborner Grundschultages mit dem Thema: Interkulturell lernen-erziehen-bilden. Universität Paderborn - Büker, Petra
Februar 2003

Dominating Sets in Planar Graphs: Branch-Width and Exponential Speed-Up - Fomin, Fedor V.; Thilikos, Dimitrios M. (Proceedings of the 14th ACM-SIAM Symposium on Discrete Algorithms (SODA 2003))
Graph minors theory, developed by Robertson & Seymour, provides a list of powerful theoretical results and tools. However, the wide spread opinion in Graph Algorithms community about this theory is that it is mainly of theoretical importance. The main purpose of this paper is to show how very deep min-max and duality theorems from Graph Minors can be used to obtain essential speed-up to many known algorithms on different domination problems.

Scheduling in HPC Resource Management Systems: Queuing vs. Planning - Hovestadt, Matthias; Kao, Odej; Keller, Axel; Streit, Achim (Proc. Workshop on Job Scheduling Strategies for Parallel Processing (JSSPP))
Nearly all existing HPC systems are operated by resource management systems based on the queuing approach. With the increasing acceptance of grid middleware like Globus, new requirements for the underlying local resource management systems arise. Features like advanced reservation or quality of service are needed to implement high level functions like co-allocation. However it is difficult to realize these features with a resource management system based on the queuing concept since it considers only the present resource usage. In this paper we present an approach which closes this gap. By assigning start times to each resource request, a complete schedule is planned. Advanced reservations are now easily possible. Based on this planning approach functions like diffuse requests, automatic duration extension, or service level agreements are described. We think they are useful to increase the usability, acceptance and performance of HPC machines. In the second part of this paper we present a planning based resource management system which already covers some of the mentioned features.
Keywords: High Performance Computing; Service Level Agreement; Grid Resource; Resource Management System; Advance Reservation